Ontogeny of the digestive tract of Arapaima gigas (Schinz, 1822) (Osteoglossiformes: Arapaimidae) larvae - Alcantara, Aline M. de; Fonseca, Flavio A. L. da; Araujo-Dairiki, Thyssia B.; Faccioli, Claudemir K.; Vicentini, Carlos A. [UNESP]; Conceicao, Luis E. C. da; Goncalves, Ligia U. (Wiley-Blackwell, 2019)
Early-life survival of Arapaima gigas is one of the main challenges of its farming. In this study, we described the morphological and histochemical development of the gastrointestinal tract of arapaima larvae. Larvae were collected from a pond when they started to swim to the water surface (initial day) and were housed in indoor tanks. Daily samplings (n = 10) were performed from 0 to the 11th day after the collection (DAC) and then on the 14th, 17th, and 20th DAC. On the initial day, arapaima larvae (0.05 +/- 0.01 g; 2.21 +/- 0.06 cm) had opened mouth and anus and no yolk sac. In addition, larvae presented well-developed digestive organs. Gastric glands were fully formed, with positive reactions to alcian blue (AB) pH 1.0 as well as to periodic acid-Schiff (PAS) in the simple columnar epithelium. There were folds throughout the intestine and brush border, with an AB pH of 2.5 + PAS positive mucins. From 1 to 11 DAC, larvae presented increasing concentrations of gastric glands and thickness of the stomach muscular layer. From 14 to 20 DAC, the intestine presented high-fold complexity. We suggest that arapaima larvae may be fed exogenous inert diets at a size of around 2 cm.
Keywords: digestive system; histochemistry; larvae; mucins; paiche; pirarucu